2012
DOI: 10.1007/s00535-012-0614-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of gremlin 1 correlates with increased angiogenesis and progression-free survival in patients with pancreatic neuroendocrine tumors

Abstract: GREM1 expression was correlated with tumor-associated angiogenesis and was found to be a novel prognostic marker in pancreatic NETS. Our data support a tumor suppressor role of GREM1 in pancreatic NETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 18 publications
3
37
1
Order By: Relevance
“…Others have shown that GREM1 expression was associated with angiogenesis and was inversely correlated with survival in cancer. 39 The robust angiogenic response to GREM1 in SJL mice, despite the lack of significant up-regulation of Vegf, along with the lack of suppression of angiogenesis in GREM1 mice treated with 1D11 despite the reduction in Vegf with this therapy, suggest that GREM1 may have direct angiogenic properties not requiring VEGF or TGF-b. This hypothesis is supported by recent evidence that GREM1 may directly bind the VEGF receptor.…”
Section: Discussionmentioning
confidence: 95%
“…Others have shown that GREM1 expression was associated with angiogenesis and was inversely correlated with survival in cancer. 39 The robust angiogenic response to GREM1 in SJL mice, despite the lack of significant up-regulation of Vegf, along with the lack of suppression of angiogenesis in GREM1 mice treated with 1D11 despite the reduction in Vegf with this therapy, suggest that GREM1 may have direct angiogenic properties not requiring VEGF or TGF-b. This hypothesis is supported by recent evidence that GREM1 may directly bind the VEGF receptor.…”
Section: Discussionmentioning
confidence: 95%
“…Expression of α-SMA, Desmin (DES), CD248, NG2, CD146 and platelet derived growth factor receptor-beta (PDGFRB) genes (Chen et al, [34]) was analyzed in cultured HBVPs and HUVECs growing on plastic. All markers were highly expressed in HBVPs.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…GREM1 is a novel proangiogenic factor as demonstrated by several studies (2,7). In a study by Chen et al (7) on tumorrelated angiogenesis, expression of GREM1 was shown to be correlated with increased angiogenesis in patients with pancreatic neuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that COL15A1 also serves as an endothelial marker, microvessels stained with COL15A1 were counted under light microscopy at a magnification of x 400 in 5 fields with a clear view of the lumen in randomly selected tumor tissues and normal tissues (7).…”
Section: Microvascular Densitymentioning
confidence: 99%